Love, H : the letters of Helene Dorn and Hettie Jones - Jones, Hettie; Dorn, Helene (Duke University Press, 2016)
Love, H is an intimate selection of letters from a forty-year correspondence between writer Hettie Jones and painter and sculptor Helene Dorn, who both survived their time as wives in the Beat bohemia of the 1960s and went on to successful artistic careers of their own.